Newfoundland Landsmen Sealing: Interrogating the Limits of Ecomasculinity in the Late 20th and Early 21st Centuries - Keough, Willeen (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2021)
The much-publicized debate over the Newfoundland seal fishery since the mid-1960shas marginalized the sealers’ own experiences. This article will situate the sealers’thoughts, bodies, and emotions in that sealing controversy, exploring landsmen’sperformance of respectable masculinity as humane and responsible harvesters witha legitimate place within the ecosystem of the northwestern Atlantic. It will parselandsmen discourse about an ecologically sustainable hunt that is rooted in traditionaland local knowledge and is also culturally and economically significant. In so doing,this article will challenge practitioners and theorists of ecomasculinity to have moreinclusive conversations with less-privileged rural harvesters, local economies, andresource-based ways of life.